The role of circulating tumor DNA in gynecological cancer management - Gao, Min; Yu, Pei-Yan; Li, Run-Xuan; Chen, Chen; Cong, Xiao-Feng; Liu, Zi-Ling (Frontiers in Oncology, 2026)
Ovarian cancer, endometrial cancer, and cervical cancer represent the three most prevalent primary gynecological tumors that pose a significant threat to women’s health globally. To enhance survival rates for patients with gynecological cancers, there is an urgent need to optimize disease detection and monitoring technologies aimed at improving early diagnosis, treatment efficacy monitoring, treatment guidance, and prognosis prediction. Currently, traditional methods for identifying and tracking malignant tumors primarily depend on imaging studies, supplemented by blood-based protein biomarker testing. However, these biomarkers generally exhibit limitations in terms of sensitivity and specificity. Circulating tumor DNA (ctDNA), comprising DNA fragments released by cancer cells into the bloodstream, can be detected using liquid biopsy technology. Compared to tissue biopsy, ctDNA testing offers the advantages of minimal invasiveness and continuous monitoring, thereby eliminating the need for multiple surgeries. In addition, it may detect disease recurrence or predict behavior in ways that entity organization biopsy, tumor marker monitoring, and imaging cannot. Increasing evidence indicates that ctDNA has the potential to enhance the clinical management of gynecological tumors by improving early diagnosis, monitoring treatment responses, detecting recurrences, and predicting prognosis. This review aims to summarize the application of ctDNA in gynecological cancers and provide an overview of its comprehensive research and clinical validation. Furthermore, we discuss future development directions based on existing challenges and identify areas requiring further research to elucidate the potential of ctDNA in clinical applications.